Gastroprotective effects of Erythrina speciosa (Fabaceae) leaves cultivated in Egypt against ethanol-induced gastric ulcer in rats. (10th February 2020) - Fahmy, Nouran M.; Al-Sayed, Eman; Michel, Haidy E.; El-Shazly, Mohamed; Singab, Abdel Nasser B.
Abstract: Ethnopharmacological relevance: Members of the genus Erythrina have been traditionally used in the treatment of various ailments such as inflammation and gastrointestinal disorders. Erythrina speciosa (Fabaceae) is a spiny, deciduous shrub or small tree native to Southern America in Brazil. It is cultivated in Africa and Asia. The traditional usage of E. speciosa indicated its antibacterial, analgesic, and anti-inflammatory activities. Aim of the study: Evaluation of the phytochemical constituents, gastroprotective effects and possible mechanism of action of the ethyl acetate fraction obtained from the methanol extract of E. speciosa leaves (ESLE). Materials and methods: Chemical characterization of ESLE was done using high performance liquid chromatography coupled to mass spectrometry (HPLC-MS). The gastroprotective activity of ESLE was evaluated using ethanol-induced gastric-ulcer model in rats. Rats were pre-treated with ESLE 25, 50 and 100 mg/kg 1 h before the administration of absolute ethanol. Histological analysis, mucin content, and total acidity were evaluated. The possible mechanism of action of ESLE was studied through the examination of oxidative stress and inflammatory markers, PGE2, and NF-κB, iNOS, COX-2, and HSP-70 immunoexpression. In vitro, anti- Helicobacter pylori activity of ESLE was also studied using micro-well dilution method. Results: Fourteen compounds were tentatively identified including alkaloids, flavonoids, and saponins. ESLE exerted a powerful gastroprotective effect. The pre-treatment with ESLE at different doses resulted in a significant reduction in gastric lesions and significant elevation in the mucin production. These effects could be partially mediated by the potent anti-inflammatory activity of ESLE as evidenced by the significant reduction in the immunoexpression of NF-κB, COX-2, iNOS and the reduction in the pro-inflammatory marker, TNF-α. ESLE counteracted the ethanol-induced oxidative stress by increasing the levels of depleted GSH and catalase as well as significantly attenuating the ethanol-induced lipid peroxidation tissue levels. In addition, ESLE exhibited in vitro antibacterial activity against H. pylori. Conclusions: The chemical constituents of ESLE strongly support its potent gastroprotective effect suggesting its future potential application in the management of gastric ulcer by eliminating its symptoms and causes including H. pylori . Graphical abstract: Image 1